Platform interconnection and quality incentives - Claudia Salim (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2008)
We analyze competition between two platforms with positive network externalities. Platforms can choose to interconnect or alternatively, operate exclusively. We examine how this decision will affect pricing behaviour and incentives to invest in Platform quality. We find that interconnection is aa means to reduce externalities one side exerts on the other. It changes the mode of competition for subscribers and resultsin higher subscription prices. Further, even though interconnection allows for quaality spillovers to the rival platform, it results in higher quality investment than the case of exclusive platforms. Coordination will facilitate collusion on the lowest quality levels possible if its provision is costly. For low quality costs it will lead to asymmetric networks. Therefore, interconnection without coordinated investment activities is welfare maximising.
Keywords: D43; D62; L13; 330; Two-sided markets; interconnection; investment in transaction quality; Telekommunikationsnetz; Produktqualität; Normung; Network Externalities